High-performance La-doped BCZT thin film capacitors on LaNiO3/Pt composite bottom electrodes with ultra-high efficiency and high thermal stability - He, Shangkai; Peng, Biaolin; Leighton, Glenn J. T.; Shaw, Christopher; Wang, Ningzhang; Sun, Wenhong; Liu, Laijun; Zhang, Qi (Elsevier, 2019)
Dielectric capacitors possessing large energy storage density, high efficiency and high thermal stability simultaneously are very attractive in modern electronic devices to be operated in harsh environment. Here, it is demonstrated that large energy storage density (W ∼ 15.5 J/cm3), ultra-high efficiency (η ∼93.7%) and high thermal stability (the variation of both W from 20 °C to 260 °C and η from 20 °C to 140 °C is less than 5%) have been simultaneously achieved in the La-doped (Ba0.904Ca0.096)0.9775+xLa0.015(Zr0.136Ti0.864)O3 (x = 0.0075) lead-free relaxor ferroelectric thin film capacitors deposited on LaNiO3/Pt composite bottom electrodes by using a sol-gel method. The good energy storage property of the thin film capacitors at x = 0.0075 is mainly ascribed to the diversity of the structure of the nano-clusters around the three-phases coexisting component point (Ba0.904Ca0.096)(Zr0.136Ti0.864)O3 where cubic, tetragonal and rhombohedral phases coexisted, as well as the ultra-high quality of thin film due to the utilization of the LaNiO3/Pt composite bottom electrode, making it a promising candidate for dielectric capacitors working in harsh environments.
Keywords: Dielectric capacitors; Sol-gel; Thin film; Energy storage